Review of the leafhopper genus Anaceratagallia Zachvatkin, 1946 (Homoptera: Auchenorrhyncha: Cicadellidae: Megophthalminae: Agalliini) from Russia, Kazakhstan, and Central Asia - Tishechkin, Dmitri Yu. (Zootaxa, 2020)
In Russia, Kazakhstan, and Central Asia the genus Anaceratagallia includes 14 species from two subgenera; all species except one belong to the nominotypical subgenus and can be classified into four groups according to the structure of male genitalia. The illustrated descriptions for all species are given, with male calling signal oscillograms provided for nine species. Ten new synonyms are established. Comparative investigation of morphological and acoustic characters of Anaceratagallia species showed that small differences in the structure of male genitalia and 2nd abdominal apodemes are not species-specific traits. All species studied in nature appeared to be polyphagous feeding on different species of herbaceous dicotyledons. It is assumed that closely related species within each group of the subgenus Anaceratagallia arose as a result of allopatric speciation and became secondarily sympatric due to subsequent range expansions.